Iconographic Classroom with the PACIE Methodology for English Language Teaching - Orbe Guerrero, Valeria Stacy (2025)
The main objective of this research is to propose the implementation of an iconographic classroom using the PACIE methodology as a pedagogical and innovative solution for teaching English to A2.1-level students of the accounting major in the virtual modality at Universidad Politécnica Estatal del Carchi, Tulcán, during the November 2024 - February 2025 academic period. This proposal seeks to address the limitations identified in the initial diagnostic assessment, which revealed low performance in the skills of speaking (32.79%), writing (49.18%), reading (42.50%), and listening (38.77%). These results correspond to a low or minimal A1 level, according to the CEFR. To conduct this study, a mixed research approach was used, with a descriptive and field design. For collecting the results, a structured diagnostic test was used to assess students' language skills, as well as a Likert scale survey of teachers in order to identify perceptions of the effectiveness of the PACIE methodology and the use of iconographic resources. Findings showed that despite acceptable performance in vocabulary and grammar, communicative skills remained below 50%, particularly in speaking, writing, listening, and reading. On the other hand, based on the data obtained from the survey of 33 teachers, there was a high level of acceptance for its implementation. Therefore, the instructional design was developed considering several key elements organized into phases, considering the diagnosis and analysis of needs, definition of learning objectives, selection of content, resources, and tools, evaluation, and feedback aligned with the CEFR standards for level A2.1. Lastly, the classroom was designed on the Milaulas platform based on PACIE principles, to promote autonomous, collaborative, and meaningful learning, along with strengthening cross-curricular skills and motivating students in virtual environments. It is concluded that this pedagogical model can be replicated in other educational contexts, considering it a key tool for innovation in virtual language teaching.